Lugar de índio: processos subjetivos e permanência simbólica de estudantes indígenas na Universidade Estadual de Feira de Santana - Zatti, Fernanda Almeida Ribeiro (2020)
The expansion of vacancies in higher education institutions, with affirmative action policies, enabled the insertion of young people in universities that previously did not see this access as a possible reality. The most expressive indigenous presence in this context is recent and with it comes the need to build knowledge for the understanding of this new student and about his university experience. Therefore, the present study is the result of my professional practice as a psychologist at the State University of Feira de Santana - UEFS and sought to understand the subjective processes and symbolic permanence of indigenous students in the institution. To achieve this goal, a contextualization of these students was made, through institutional data and the application of a structured questionnaire to indigenous students enrolled at the beginning of the research, and a qualitative analysis of the narratives of four indigenous students about their experiences and perceptions about the university, conducted through interviews, individual productions (written and imagery) and focus group. From the research, it was possible to perceive the subjective processes that student’s experience, indicating the transitions experienced during this path, and proposals were indicated to be developed to strengthen the permanence of these students in higher education. The research demonstrated that guaranteeing access does not exhaust the struggle in search of equality and inclusion, pointing out the need for further study of policies of symbolic permanence, taking into account the specificities of indigenous students at the university, their territoriality, their religious rituals, cultural and regional differences, among others. In addition, an alert for the various agents of the academic community (students, teachers and civil servants) to understand the potential of this environment, with all its diversity, so that they can promote a truly inclusive institution.